Ficus deltoidea Jack: A Review on Its Phytochemical and Pharmacological Importance. (17th March 2014) - Bunawan, Hamidun; Amin, Noriha Mat; Bunawan, Siti Noraini; Baharum, Syarul Nataqain; Mohd Noor, Normah
Abstract : Ficus deltoidea Jack (Moraceae) has had a long history of use in traditional medicine among the Malays to alleviate and heal ailments such as sores, wounds, and rheumatism and as an after-birth tonic and an antidiabetic drug. Modern pharmacological studies demonstrated that this plant has a wide variety of beneficial attributes for human health. Despite its importance, a review of this species has not been published in the scientific literature to date. Here, we review and summarize the historic and current literature concerning the botany, traditional uses, phytochemistry, pharmacological effects, and toxicity of this wonder plant. This summary could be beneficial for future research aiming to exploit the therapeutic potential of this useful, medicinal species.